СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО ​
Ответ
4 (1 оценка)
1
Evgenia4836 3 недели назад
Светило науки - 5174 ответа - 23701 помощь

Ответ:

Пошаговое объяснение:

а²= а*а

а³= а*а*а

(-а)²= а²

(-а)³= -а³

1) (-11)²= 121

2) (-0,7)²= 0,49

3) (-2/5)²= 4/25

4) (-4)³= -64

5) (-0,2)³= -0,008

6) (-1/2)³= -1/8

7) (-10)²+97= 100+97= 197

8) (-0,9)²-1 = -0,81-1= -1,81

9) (-2/3)³-1= -8/27-1= -35/27